An oligosaccharyltransferase from Leishmania major increases the N‐glycan occupancy on recombinant glycoproteins produced in Nicotiana benthamiana. Issue 10 (25th March 2018) - Castilho, Alexandra; Beihammer, Gernot; Pfeiffer, Christina; Göritzer, Kathrin; Montero‐Morales, Laura; Vavra, Ulrike; Maresch, Daniel; Grünwald‐Gruber, Clemens; Altmann, Friedrich; Steinkellner, Herta; Strasser, Richard
Summary: N‐glycosylation is critical for recombinant glycoprotein production as it influences the heterogeneity of products and affects their biological function. In most eukaryotes, the oligosaccharyltransferase is the central‐protein complex facilitating the N‐glycosylation of proteins in the lumen of the endoplasmic reticulum (ER). Not all potential N‐glycosylation sites are recognized in vivo and the site occupancy can vary in different expression systems, resulting in underglycosylation of recombinant glycoproteins. To overcome this limitation in plants, we expressed LmSTT3D, a single‐subunit oligosaccharyltransferase from the protozoan Leishmania major transiently in Nicotiana benthamiana, a well‐established production platform for recombinant proteins. A fluorescent protein‐tagged LmSTT3D variant was predominately found in the ER and co‐located with plant oligosaccharyltransferase subunits. Co‐expression of LmSTT3D with immunoglobulins and other recombinant human glycoproteins resulted in a substantially increased N‐glycosylation site occupancy on all N‐glycosylation sites except those that were already more than 90% occupied. Our results show that the heterologous expression of LmSTT3D is a versatile tool to increase N‐glycosylation efficiency in plants.